Fieldbus and networking in process automation - Sen, Sunit Kumar (Boca Raton : CRC Press, 2021)
Over the last two decades, fieldbus has totally revolutionized the way communication takes place in the fields of process control, automation, and manufacturing industries. Recent introduction of real-time fieldbuses has opened up its application in multi-axis motor control and other time-critical applications. Fieldbus is designed to ensure easy interoperability, smarter network designs, increased data availability, and lessened stress on the design aspects of safety protocols. This second edition of Fieldbus and Networking in Process Automation discusses the different facets of fieldbus technology including design, wiring, installation, and commissioning as well as safety aspects in hostile application areas. The book: Explains basic communication principles and networking--a must for understanding fieldbuses Considers the advantages and shortcomings of individual fieldbuses Provides a broad spectrum of different fieldbuses used in both process control and manufacturing industries in a precise and to-the-point manner Introduces Common Industrial Protocol (CIP), EtherNet/IP, EtherCAT, SERCOS III, Powerlink, and Profinet IRT, which are mostly sought after in control and automation fields Discusses hard real-time communication in a succinct manner--so essential in today's multi-axis motor control systems Updates and streamlines the extra details from the original book to make it more concise and reader friendly Sunit Kumar Sen, a member of IET, holds advanced degrees from St Xavier's College and University of Calcutta, both in Kolkata, India. He was an ex-professor in the Instrumentation Engineering section of the Department of Applied Physics, University of Calcutta, and taught courses in digital electronics, communication, industrial instrumentation, microprocessors, electrical networks, and fieldbuses. He was the head of the Department of Applied Physics and University Science Instrumentation Center from 2008-2010 at the University of Calcutta. Previously, he was assistant manager, instrumentation (oprn.) at the Bokaro Steel Plant, Jharkhand, India, under the Steel Authority of India (SAIL). He has already written four books in the areas of instrumentation, microprocessors, and industrial automation technologies. He has been published in approximately 70 national and international journals and conferences.
Previous edition: 2014.
Chapter 1 Data Communication..............................................................1 Chapter 2 Networking...........................................................................25 Chapter 3 Network Models...................................................................35 Chapter 4 Networks in Process Automation.........................................53 Chapter 5 Fieldbuses.............................................................................63 Chapter 6 Highway Addressable Remote Transducer (HART)................ 75 Chapter 7 Foundation Fieldbus.............................................................89 Chapter 8 PROFIBUS......................................................................... 119 Chapter 9 Modbus and Modbus Plus.................................................. 145 Chapter 10 CAN Bus............................................................................ 157 Chapter 11 DeviceNet........................................................................... 163 Chapter 12 AS-i.................................................................................... 169 Chapter 13 Seriplex............................................................................... 175 Chapter 14 Interbus-S........................................................................... 179 Chapter 15 ControlNet.......................................................................... 189 Chapter 16 Common Industrial Protocol.............................................. 201 Chapter 17 Ethernet and Ethernet/IP.................................................... 213 Chapter 18 EtherCAT...........................................................................225 Chapter 19 Sercos III............................................................................237 Chapter 20 Ethernet Powerlink............................................................. 251 Chapter 21 Profinet IRT........................................................................257 Chapter 22 Intrinsically Safe Fieldbus Systems....................................265 Chapter 23 Wiring, Installation, and Commissioning..........................277 Chapter 24 Wireless Sensor Networks..................................................303 Chapter 25 WirelessHART (WHART)................................................ 317 Chapter 26 ISA100.11a..........................................................................343
OCLC-licensed vendor bibliographic record.
Keywords: Process control -- Data processing; Fieldbus (Computer network protocols); Automation; Intelligent control systems; COMPUTERS / Networking / General